Detection of oral squamous cell carcinoma metastasis with cathepsin D: An immunohistochemical approach - Seema Kapoor; Geet Priya Kaur; Pranav Sikka (Wolters Kluwer Medknow Publications, 2014)
Background: The lysosomal protease cathepsin D (CD) has been associated with tumor progression in malignant tumors including oral squamous cell carcinoma (OSCC). The purpose of this study was to find out any association between the CD and lymph node metastasis and to study the correlation of CD with various clinicopathological parameters to aid in assessment of its role as a prognostic indicator. Materials and Methods: Immunohistochemical staining was performed on 20 OSCC samples with polyclonal antibody against CD. Positive results indicative of the presence of CD were further analyzed to determine any correlation between the CD and other clinicopathological parameters. Pearson Chi-square analyses, Spearsman correlation coefficient, Mann-Whitney test, Kruskal Wallis test and student t test were used for statistical analysis (P < 0.05). Results: Patients with lymph node metastasis showed statistically significant increase in CD expression (P < 0.01). Increasing tumor size seemed to correlate with increased CD expression (P < 0.05). Conclusion: Based on its association with other clinicopathological variables, CD expression can be used for the assessment of patient survival in cases of OSCC.